STUDI POTENSI ENERGI ANGIN KOTA BANDA ACEH DENGAN METODE RAYLEIGH DISTRIBUSI - Wahyu Priyanto; Ira Devi Sara; Rakhmad Syafutra Lubis (J-Innovation, 2018)
Modeling wind speed variations is a very important requirement in determining energy potential to find out typical winds speed in an area. Data obtained from the average wind speed in Banda Aceh City of Aceh Province were correlated from NASA Data Access (Prediction of Worldwide Energy Resource) for 1 (one) year. Wind speed data is analyzed statistically to determine the potential of wind energy as a small scale power plant, which is grouped on an annual basis. Wind power distribution is obtained by the Rayleigh distribution function method, with the aim of predicting wind energy produced as a wealth study for designing small-scale wind turbine power plants. The calculation results show that by using the annual clustering Rayleigh function method, cumulative distribution and probability density functions will be obtained. The available power from the winds of the Banda Aceh region for 1.4 m2 turbines sweapt area with an average wind speed of 4.4 m/s produces an energy potential of around 237.9 kW-hrs per year. The Rayleigh function of this distribution uses estimated parameters, which are expected to provide a more accurate prediction of the average energy produced for a region. The annual variations in wind speed and power density functions described in this article are very useful to ensure that the generator is selected and determined appropriately, so that an optimal wind turbine power plant will be obtained.